Perspektiven der Pädagogik bei Unterstützungsbedarf der emotionalen und sozialen Entwicklung - Laubenstein, Désirée (In: Zeitschrift für Heilpädagogik, 67, jahrgang, Nr. 11)

Das Praxissemester als Ort religionspädagogischer Professionalisierung - Caruso, Carina; Hengesbach, Rudolf (SEMINAR – Lehrerbildung und Schule)

„Nein, ich war nicht beim Sport“ - Klingsieck, Katrin B.; Weigelt, Matthias (Zeitschrift für Sportpsychologie)
Zusammenfassung. Die Rolle von Prokrastination, dem unnötigen Aufschieben von intendierten Tätigkeiten wider besseren Wissens, ist bisher noch nicht für die Domäne Sport untersucht worden. Ziel dieses Beitrags ist es daher, den Zusammenhang zwischen Prokrastination und dem wöchentlichen Sporttreiben zu untersuchen. In einer Onlinestudie mit 167 Sportstudierenden (92 Frauen; Durchschnittsalter = 21 Jahre) wurden dazu die allgemeine sowie die sportspezifische Prokrastination in Relation zu den Persönlichkeitsvariablen Gewissenhaftigkeit und Neurotizismus, der volitionalen Variable Handlungskontrolle, der motivationalen Variable Selbstwirksamkeit im Sport sowie der Häufigkeit sportlicher Aktivitäten untersucht. Die Ergebnisse der Korrelations-, Regressions- und Mediationsanalysen zeigen, dass Prokrastination auch für sportliche Akvtivitäten ein ernst zu nehmendes Phänomen sein kann. Darüber hinaus ermutigen sie zur Entwicklung einer sportspezifischen Prokrastinationsskala.

On the Measurement of Procrastination: Comparing Two Scales in Six European Countries - Svartdal, Frode; Pfuhl, Gerit; Nordby, Kent; Foschi, Gioel; Klingsieck, Katrin B.; Rozental, Alexander; Carlbring, Per; Lindblom-Ylänne, Sari; Rębkowska, Kaja (Frontiers in Psychology)

Positive Auswirkungen (gesundheits-)psychologischer Ausbildungsinhalte im Studium auf die arbeitsbezogenen Belastungsmuster von Referendarinnen und Referendaren mit dem Unterrichtsfach Sport - Weigelt, M.; Lex, H.; Wunsch, K.; Kämpfe, A.; Klingsieck, Katrin B. (Sportunterricht)

Academic Procrastination: Psychological Antecedents Revisited - Steel, Piers; Klingsieck, Katrin B. (Australian Psychologist)

Grammatisches Lernen

Sprachgeschichtsforschung im Horizont von Nähe und Distanz - Tophinke, Doris (Zur Karriere von Nähe und Distanz)

Grammatisches Lernen (Basisartikel) - Feilke, Helmuth; Tophinke, Doris (Praxis Deutsch)

Graffiti. Formen, Traditionen, Perspektiven - Papenbrock, Martin; Tophinke, Doris (Sprache in der Kunstkommunikation)

"Es war einer dieser Nächte ..." Writer Storys zwischen Fiktionalität und Faktualität - Papenbrock, Martin; Tophinke, Doris (Der Deutschunterricht)

„In den tiefsten Winkeln unserer Betonwälder tanzen die Namen ein farbenfrohes Fest und wir tanzten bis in die Morgenstunden“ – Zur praktischen Kultur des Graffiti - Tophinke, Doris (Kommunikative und sprachliche Praktiken)

Science teaching processes - Introduction to strand 3. In Lavonen, J., Juuti, K., Lampiselkä, J., Uitto, A., & Hahl, K. (eds.), Electronic Proceedings of the ESERA 2015 Conference. Science education research: Engaging learners for a sustainable future.

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Förderschwerpunkte Sozial-Emotionale Entwicklung und Lernen (SEELe): Zusammensetzung der Schülerschaft an Förderschulen und im inklusiven Unterricht – eine Pilotstudie - Laubenstein, Désirée

Leadership Orientation and the recontextualisation of inclusive education: The principal’s role in mainstreaming schools in Rhineland-Palatinate. Symposium mit Köpfer, A., Sturm, T. & Feyerer, E - Scheer, D.; Laubenstein, Désirée; Lindmeier, C.

Students with Special Educational Needs (SEN) in Learning Disabilities (LD) and Emotional and Behavioural Disorders (EBD) in Rhineland-Palatinate: Social Skills, Behavioural Difficulties and Social Status. - Laubenstein, Désirée; Scheer, D.

Low-Power, Ultra-compact, Fully-differential 40Gbps Direct Detection Receiver in 0.25μm Photonic BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Meister, Stefan; Knoll, Dieter; Lischke, Stefan; Zimmermann, Lars; Meuer, Christian (IEEE Group IV Photonics Conference)
Recently electronic-photonic integrated circuits (EPIC) technology platforms became available [1] which allow fabrication of very compact and fast monolithic receivers. However, although the cointegration of electronics and photonics on the same chip allows for novel circuit topologies which could help to improve circuit performance quite often transmitter and receiver circuit design is using more or less conventional approaches. We propose a novel architecture that effectively utilizes the benefits of the EPIC technology such as: very short interconnects between the photodiode and the amplifier, symmetrical and compact photodiode structure with low operating voltages. Our architecture shown in Fig. 1 features fully-differential input stage, automatic biasing of the photodiode, DC coupling between diode and transimpedance amplifier (TIA) and very small footprint.

Recent Advances in Millimeter-Wave-and Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Microelectronics Seminar)

Electronic-Photonic System-On-Chip - Scheytt, Christoph (DFG Rundgespräch:"Disruptive system concepts using electronic-photonic integration)